Dosimetric advantages of dual-layer MLC in hypofractionated stereotactic radiotherapy for multiple brain metastases: a comparative study with single-layer MLC - Zhong, Changyou; Bi, Suyan; Yu, Haidong; Jiang, Zhendong; Dai, Zhitao (Frontiers in Oncology, 2025)
PurposeThis study aims to evaluate the dosimetric impact of dual-layer-stacked multi-leaf collimators (MLCs) by comparing stereotactic radiotherapy (SRT) plans for multiple brain metastases (BMs) using the dual-layer MLC of the Halcyon 3.0 system against the single-layer MLC of the Versa HD system.MethodsEighteen patients with multiple BMs were retrospectively selected for this study. For each patient, five SRT plans were generated: two using the dual-layer MLC (Halcyon 3.0) and three using the single-layer MLC (Versa HD, comprising two coplanar and one non-coplanar plan). All plans were optimized under identical conditions, with dose normalization ensuring 95% of the target volume received 100% of the prescribed dose. Dosimetric parameters such as D2%, Dx (the dose of x percent volume), D98%, Dmean, conformity index (CI), homogeneity index (HI), and gradient index (GI) for the planning target volume, as well as Dmax, Dmean, and volume-specific doses (VX) for organs at risks (OARs), were analyzed. Additionally, treatment time, monitor units (MUs), and radiobiological indices, including equivalent uniform dose (EUD), tumor control probability (TCP), and normal tissue complication probability (NTCP), were assessed.ResultsThe Halcyon 3.0 plans with dual-layer MLC demonstrated superior dosimetric outcomes compared to Versa HD coplanar plans, particularly in reducing V5, V10, V20, V24, and Dmean for normal brain tissue. The GI of Halcyon 3.0 plans was comparable to that of Versa HD noncoplanar plans. Furthermore, Halcyon 3.0 plans achieved lower EUD and NTCP values for both brainstem and normal brain tissue, matching the performance of Versa HD non-coplanar plans. These findings highlight the efficacy of dual-layer MLC in achieving dosimetric results similar to non-coplanar techniques while offering enhanced protection to OARs.ConclusionThe dual-layer stacked MLC of the Halcyon 3.0 system provides comparable OAR sparing and dose gradients to non-coplanar Versa HD plans in single-isocenter hypofractionated SRT for multiple BMs, with significant improvements over coplanar Versa HD plans. This suggests that Halcyon 3.0 could be a preferred option for such treatments when non-coplanar setups are not feasible.